Field test and numerical modeling of vehicle impact on a boulder with impact-induced fractures. Issue 1 (March 2016) - Zhou, Yaneng; Reese, Lynsey; Qiu, Tong; Rado, Zoltan
Landscape Vehicle Anti-Ram systems, typically comprising natural materials such as boulders, are effective in protecting sensitive structures against threats. However, fracturing of these materials under vehicular impact can be detrimental to the performance of Landscape Vehicle Anti-Ram systems. This study presents a field-scale crash test and LS-DYNA modeling of a Landscape Vehicle Anti-Ram system subjected to vehicular impact. The Landscape Vehicle Anti-Ram system consisted of three boulders connected through a reinforced concrete foundation embedded in compacted American Association of State Highway and Transportation Officials soil. The central boulder fractured upon vehicular impact. An advanced material model was adopted to model the rock fracture and crushing. The global response of the truck, including cab deformation and dynamic penetration, from the simulation showed good agreement with the field observations. The failure patterns of the boulder, including the fracture plane and minor crushing, also agreed well with the field observations. Through a parametric study, the dynamic penetration of the truck is found to be influenced by the elastic modulus and fracture energy of the boulder, and the Landscape Vehicle Anti-Ram system is more effective with a stiffer and tougher boulder.